Investigation of the Effect of Boundary Condition on the Property of TRIP Steel by Finite Element Simulation. Issue 4 (May 2019) - Li, J.H.; Deng, H.P.; Yu, S.
Abstract: TRIP (Transformation induced plasticity) steel combined high strength and high plasticity perfectly, which depend on the micro structure of the material greatly. Residual austenite plays an important role on the micro material transformation and macro property. Different boundary condition makes different stress and strain field of the TRIP steel and induced different residual austenite transformation. Under different compression stress, the residual austenite transformation was different, to predict the micro transformation behavior, investigation of the macro stress character was necessary. Finite element simulation was carried out in this paper to investigate the stress filed of TRIP steel under different boundary condition to predict the micro residual austenite transformation and macro property development.